Uganda Economic Update, 14th Edition, February 2020 : Strengthening Social Protection to Reduce Vulnerability and Promote Inclusive Growth - World Bank (World Bank, Washington, DC, 2020)
Following the release of new GDP estimates, nominal GDP for FY18/19 increased and the structure of the economy has changed. In October 2019, the Uganda Bureau of Statistics (UBOS) released new GDP estimates, updating the base year for estimating economic activity to 2016/17 from 2009/10. As a result, nominal GDP for FY18/19 was revised upwards from USh 109,945 billion to USh 128,499 billion. Furthermore, the share of industry in GDP has increased from about 20 percent to almost 30 percent. At the same time, there has been a drop in the share of services from about 58 percent to 46 percent. Manufacturing has doubled its share from about 8 percent to over 16 percent of GDP, whilst information and communications (IC) has fallen from 12 percent to just under 2 percent of GDP. Real GDP grew by 6.5 percent in FY18/19, maintaining the rebound in economic activity over the last two years. This has been driven by strong levels of domestic consumption and sustained levels of public and private investment. Net FDI inflows shot up to 5.1 percent of GDP in FY18/19 from 3 percent of GDP the previous year. The construction sector continues to grow at double-digit levels. There has been a jump in manufacturing growth supported by recent expansions in the sector, including investments in new factories. Agriculture was boosted by another decent harvest and a strong rebound in fisheries. Levels of GDP growth of about 6 percent and above are expected over the medium-term, driven by consumption spending, intensified private and public investments in infrastructure for industrialization, electricity transmission, and preparation for oil extraction. Still, this growth is not high enough for Uganda’s lower middle-income status and poverty reduction ambitions.